Revitalisasi Bahasa Daerah Tarlawi dalam Pendidikan Islam Sebagai Kearifan Lokal Budaya Bima - Salam, Abd (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to analyze the role of Tarlawi local language revitalization in strengthening Islamic education and preserving local wisdom values in Wawo District, Bima Regency. The method used in this research is a qualitative study with a phenomenological approach, data collected through interviews, observations, and documentation of traditional leaders, educators, and local communities who have relevance to this research. The results showed that Tarlawi language functions not only as a means of communication, but also as an educative and spiritual medium that contains noble values such as mutual cooperation (tutan dampa riman dadi), respect for teachers (kanemba guru, then kanemba Allah), and other social and religious ethics. This language has a significant role in shaping learners' character and strengthening the community's cultural identity. This research recommends the integration of Tarlawi language into the Islamic education curriculum, local culture-based teacher training, and the development of contextual teaching materials. The revitalization of this local language has proven to be a bridge between character education and the preservation of Islamic values that live in the local culture of the Wawo community.